Decision Making under Ignorance and Product Disclosure: Implications in Buying Insurance - Mendes da Silva, Wesley (2022)
Purpose – The subject of making choices under risk has been studied based on the assumption that decision makers are fully informed. However, in real life situations individuals frequently need to make choices without the benefit of essential information. This study analyzes decision making in the absence of information about the probabilities of losses and potential impacts, which constitutes a context of ignorance, or alternatively making choices under risk or uncertainty. Theoretical framework – This study is supported by theoretical aspects related to decision making under ignorance, specifically within the context of buying insurance. Design/methodology/approach – We used One Way ANOVA and regressions based on the data collected from two experiments regarding the willingness to acquire extended warranties for electronic equipment, which involved the participation of over 130 volunteers. Findings – Our findings suggest that the absence of economic information – deficient disclosure – makes the cost of insurance relevant to the consumer and is negatively associated with the propensity to acquire it. In addition, the cost of repairs and the probability of equipment breaking increase the propensity to acquire an extended warranty. Practical & social implications of research – By making information relevant to consumption decisions and accessible in a transparent manner, agents can induce a surge in consumption, making the market more efficient and society more resilient in the face of risks. Originality/value – This study may be the first to provide empirical evidence regarding the purchase of insurance within a context of ignorance in emerging markets.  Keywords – choices under ignorance, insurance, risk aversion, uncertainty, resilience.